Improvement of Text Information Processing Quality in Documents Processing Systems - Akhatov, A.R.; Jumanov, I.I. (2006 2nd IEEE/IFIP International Conference in Central Asia on Internet, 2006)
Methods, models, algorithms and software for improvement of typewritten texts processing quality at the stages of their preparation, input, transmission and processing have been developed, and also practical use of the researches results in the office-work automation systems has been carried out. The basic processes of information processing in the systems of enterprises office-work have been investigated, rules of work are formalized mathematically and application efficiency of program methods for errors control in typewritten texts has been analyzed. Principal bases of construction of ways of detection and errors correction in typewritten texts have been investigated at the expense of artificial and natural redundancy and algorithms and functional program modules of preparation stages, input, scanning and recognition, the spelling control have been developed. In new statement of error control problems, theoretical techniques of their decisions have been received.